2004
DOI: 10.1007/s11137-005-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of UO2 in a room-temperature ionic liquid in the presence of AlCl3

Abstract: A study was made of interaction between AlCl 3 and room-temperature ionic liquid (RTIL) [C 8 H 15 N 2 ][N(SO 2 CF 3 ) 2 ], or BuEtIm!Tf 2 N, and of anodic dissolution in RTIL of UO 2 and of a simulated oxide fuel at 297!302 K, depending on the AlCl 3 concentration. It was shown that anodic dissolution of UO 2 pellets and a UO 2 !Al mixture in RTIL yields soluble uranium species. Potentiostatic electrolysis of the resulting solutions can yield uranium compounds at the cathode, though with low current efficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Our results showing the presence of rare earth oxychlorides in MgCl 2 -NaCl-KCl eutectic are also substantiated by the XPS of cerium oxychloride [10] [19,20]. The formation of CeOCl and NdOCl has also been reported by Ogawa and Minato [24] and Smolenskii et al [25,26].…”
Section: Cyclic Voltammetry Of Laocl and Ndocl In Mgcl 2 -Nacl-kcl Eusupporting
confidence: 86%
“…Our results showing the presence of rare earth oxychlorides in MgCl 2 -NaCl-KCl eutectic are also substantiated by the XPS of cerium oxychloride [10] [19,20]. The formation of CeOCl and NdOCl has also been reported by Ogawa and Minato [24] and Smolenskii et al [25,26].…”
Section: Cyclic Voltammetry Of Laocl and Ndocl In Mgcl 2 -Nacl-kcl Eusupporting
confidence: 86%
“…The electron transfer process at the glassy carbon electrode is similar to what has been observed by Smolenskii et al [6]:…”
Section: Analysis Of the Cathodic Peaks I Cata And I Catbsupporting
confidence: 85%
“…Smolenskii et al [6] have also reported that the probability of formation of cerium oxo ions in alkaline earth chloride based melts is higher compared to that in alkali chloride based melts. Therefore, the formation of CeOCl should be more probable in MgCl 2 -NaCl-KCl eutectic in Cl 2 /O 2 atmosphere which is in line with our observations.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations